Legal Review of Defamation Case (Analysis of Decision of Surabaya High Court Number 528/Pid/2013/Pt.Sby) - Yunni Widhi Astuti; Arief Budiono (Universitas Muhammadiyah Surakarta, 2025)
Defamation is one of the many legal issues arising from the realm of cyberspace. There are various reasons behind the emergence of defamation issues. Often, defamation receives different interpretations under the prevailing law. This research is a normative juridical study examining the application of legal norms to a specific event. Legislative approach and literature study approach are combined through the utilization of available data. Secondary data sources consisting of primary, secondary, and tertiary legal materials are well-managed through descriptive analysis methods to address the issues under review. The objectives of this research include: 1) Understanding the legal basis related to defamation offenses; and 2) Understanding the judges' considerations in criminal decisions related to defamation, with a case study of the decision of the Surabaya High Court Number 528/PID/2013/PT.Sby. The research findings indicate that the Panel of Judges, in deciding criminal cases committed by five Defendants, must first consider the legal provisions stipulated in Article 311 of the Criminal Code. At least there are 3 (three) elements comprising the article. When the elements include, Any Person / Every Person, intentional element, and attacking the honor / good name element. The Panel of Judges felt that the actions of the Defendants had fully met the elements of this article, thus the judge's decision of 6 (six) months imprisonment was in accordance with the applicable law. In addition to considering the criminal articles, the Panel also considers other aspects such as the appeal memory, timeliness, and law enforcement. All considerations are then examined and result in a decision as it should be. The application of the law in line with norms is an obligation that must be fulfilled by the Panel of Judges in order to create social justice that benefits the community.